2015
DOI: 10.1016/j.jclepro.2015.05.033
|View full text |Cite
|
Sign up to set email alerts
|

The use of hydrogen to separate and recycle neodymium–iron–boron-type magnets from electronic waste

Abstract: The rare earth metals have been identified by the European Union and the United States as being at greatest supply risk of all the materials for clean energy technologies. Of particular concern are neodymium and dysprosium, both of which are employed in neodymium-iron-boron based magnets. Recycling of magnets based on these materials and contained within obsolete electronic equipment, could provide an additional and secure supply. In the present work, hydrogen has been employed as a processing agent to decrepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(70 citation statements)
references
References 17 publications
(18 reference statements)
2
68
0
Order By: Relevance
“…The magnets from hard disc drives have 10-20 g and are covered with Ni coating. These results are with good agreement to the work of Walton et al [4]. The medical device magnets are larger but free of coating.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The magnets from hard disc drives have 10-20 g and are covered with Ni coating. These results are with good agreement to the work of Walton et al [4]. The medical device magnets are larger but free of coating.…”
Section: Discussionsupporting
confidence: 91%
“…The mass of the examined HDDs magnets varies between 10 and 20 g, depending on their size, which is iden- tical to the results reported by Walton et al [4]. The chemical composition of the magnets is dominated by iron (65±1 wt%) and neodymium (30±2 wt%).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This lack of attention can be explained by the much lower rare-earth content of the bonded magnets compared to that of sintered magnets, as well as by the fact that the presence of the polymeric binders or resins makes direct recycling routes (such as hydrogen decrepitation) difficult. 25,26 Recycling of resin-bonded magnets requires a twofold approach: (i) successful separation of polymer from the metallic fraction and (ii) preserving the magnet powder by preventing its undesired interaction with the polymer (e.g. carbon diffusion) or, if any, solvent(s) for separation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that hydrogen can efficiently be used to separate NdFeB magnets from HDD scrap [6,7]. NdFeB magnets become demagnetised when reacted with hydrogen, thus allowing the powder to be separated much more readily.…”
Section: Introductionmentioning
confidence: 99%